Narrative in Medicine and History: how fiction reminds us of who we are - Magalhães, Susana (Advances in Social Sciences Research Journal, 2016)
Reading enhances our imagination, our narrating and listening skills, our capacity to deal with time and space, thus enlightening our ethical self-awareness as human beings. The key to know how to deal with theoretical principles and practical cases lies in hermeneutics, since a demanding ethical position requires a demanding hermeneutical procedure. Based on the novel The Storyteller, by Jodi Picoult, this essay aims at stressing the role of literary narratives in the field of Bioethics if one wants to focus on the right questions instead of searching for the one correct answer. The reading of this novel reminds us of the importance of telling one’s story in order to perceive our own identity, in order to deal with the pain of remembering and so that we may be able to forgive and to promise. The Storyteller, a story built of stories by different voices, focuses our attention on the work of memory and narrative, reminding us of the thought provoking book by Hannah Arendt, The Human Condition, and allowing us to bring in Paul Ricouer’s theory of the identity in Soi-Même comme un Autre, as well as The Wounded Storyteller by Arthur W. Frank.The intersubjective dimension of therapeuticrelationships and the relevance of narrative knowledge in health care recognized by Narrative Medicine demand from the health professionals the development of the skills of a storyteller and those of a story listener/reader. Reading The Storyteller makes us face the pillars of Narrative Medicine without focusing on health issues, by making us instead read about storytellers while we are asked to be story-listeners and story-builders.